Abolir les frontières dans la classe ? - Bérengère Kolly (Recherches en Éducation)
To question the bondaries at school can be carried out in multiple forms: between the different school spaces, temporal boundaries between the different educational times, borders, finally, related to the contents of lessons. This text proposes to study the borders inside the classroom, enclosed and limited space, but not homogeneous. If borders are also places of passage, thresholds, how can one envisage the threshold effects within the class space, considering them as educational stakes? What effects could the abolition of these same borders have in a class? We propose to grasp these issues in an unusual way, starting this text with a succinct description of drawn maps of movements, student paths and a teacher in two classes (Montessorian and related practices) at abolished borders. These cartographies will then be confronted with an opposite model, disciplinary, as archetype of a functioning on rigid and impassable borders. By reintroducing the notions of threshold and limit, we will finally draw that could be the conditions presiding over the abolition of borders in the classroom, stressing the importance of making this space habitable and inhabited.